Experimental Performance and Comfort Analyses of Photovoltaic Thermoelectric System in a Room Air-Conditioning Application - Looi, K.K. (Taylor and Francis Ltd., 2021)
In this study, the cooling and dehumidification performance of a photovoltaic powered thermoelectric air conditioning system is investigated under tropical climate. The system is first investigated under a controlled environment with different flow arrangements of the hot junction cooling air stream. Better temperature reduction was observed when the cross-flow arrangement is used. Besides, it delivered the best reduction when 1.7 A current level is supplied to each thermoelectric module (TEM). The system performance was then investigated in a 3.6 m3 room application under real weather conditions. When 1.7 A current level supplied to each TEM, it delivered 181 W and 0.14 ltr/hour average cooling load and moisture removal rate, respectively. The corresponding indoor room temperature is 4 °C less than the unconditioned reference room, 7 to 7.6 °C lower than the outdoor in the afternoon, and the indoor relative humidity varies between 58 to 83. The indoor thermal comfort analysis indicated that the indoor modified predicted mean vote is 0.24 and classified as Class A in the ISO thermal acceptability, coupled with 26.6 of mean dissatisfaction. Hence, the photovoltaic thermoelectric cooling system could be a potential option to substitute the conventional air conditioning system as it is Freon-free and no moving parts. © 2020 Taylor & Francis Group, LLC.